Synode over gewetensvrijheid Een nauwgezet onderzoek in de vergadering gehouden in het jaar 1582 te Vrijburgh - Coornhert, D.V (Bibliotheca Dissidentium Neerlandicorum|Amsterdamse Gouden Eeuw Reeks, 2008)
This book (A Conclave on the Freedom of Conscience) is an account of a fictitious dialogue on religion. Coornhert depicts representatives from the various religious camps whom he sometimes cites literally (including Beza, Calvin, Du Plessis-Mornay and Bullinger). Gamaliel (a pseudonym for Coornhert) is the impartial and knowledgeable referee. This book is not only an important work of its era. Its scope, aim, promotion of religious tolerance, and its wealth of arguments can be of great added value to the current debate on tolerance. Dirk Volkertzoon Coornhert (1522-1590) was a renowned publicist and supporter of Willem van Oranje. The Bibliotheca Dissidentium Neerlandicorum publishes works on the non-coformist history of the Netherlands (religious, philosophical and artistic) of approximately 1350 until the present day. These works of various non-conformist authors are published by Amsterdam University Press, under the Coornhert Stichting imprint.